Heterozygous SLC1A2 mutation in a child with early infantile seizures and global developmental delay - N., Rajeshwari; J., Prahada; A., Savitha (International Journal of Contemporary Pediatrics, 2022)
Seizures are a major neurologic disorder in infants and children. It can affect children at any age, from birth through adolescence. Early onset of seizures at birth or in the first few months of life can cause severe cerebral dysfunction. Also, recurrent and persistent seizures lead to severe cognitive and behavioral impairment in children. Hence, control of seizures is crucial for optimal neurodevelopment. Genetic aetiology of seizures is suspected in early onset recurrent seizures below one year of age, refractory to multiple anticonvulsants. Genetic testing in children with recurrent and therapy resistant seizures provides clue to aetiology, helps in treatment, has prognostic value. It also helps to estimate risk of seizure recurrence and helps avoid unnecessary investigations. We hereby report a case of early onset recurrent seizures with global developmental delay. Next generation sequencing revealed heterozygous missense mutation in SLC1A2 gene which is identified as an epileptic encephalopathy (EE) associated gene.